Structure of the Discourse in Nachdane Literature Visiting the Shrines and their Virtues in the Middle Middle and Modern Algeria « Reading the motives of authorship and trying to enact and discredit the speech - barkat, ismail. (Journal of Social Sciences and Humanities, 2021)
Reading many of the texts of the blogs of the groups of mines, it is clear that her speech is an analytical approach to the study of the history of the popular minds and beliefs of the medieval Maghreb society and modern Algeria. And anthropological, ethnographic and historical colonial, which requires careful analysis and investigation in the conclusion to reveal its intellectual potential, and understand its historical dimensions and religious phenomena, to take into account the genius and virtues of the visitation, its origin and evolution rooted within the curricula The world-renowned Sufi elite and the rooting and complexity projects it has accomplished to stabilize popular rituals, In order to obtain objective knowledge about the Algerian society and its religious and belief system, And the dimensions of the shrine shrine as a psychological, social and cultural balance factor against the challenges of the times, the indications of jobs and rituals that include all rituals and religious ceremonies, and various customs and traditions known.